Study of astrophysical S-factor, S (E) and thermonuclear fusion reaction rate, TNFRR for some α-trapped interactions - Mohammad N.; Mondal S.H.; Islam Rabiul; Khan Abdul (EPJ Web of Conferences)
Diverse types of reactions among nuclei occurring at the interior of stars which are at the accreting stage are tremendously affected by plasma environment of high density. Nuclear fusions at very low energy end (~ keV), much below the mutual Coulomb potential barrier, play a pivotal role in the Big-Bang nucleosynthesis of nuclei of lower masses. Mechanism of nuclear fusion reactions can be successfully described by quantum mechanical tunnelling through the effective mutual Coulomb barrier of interacting nuclei. Computation of some astro-nuclear observables, such as the astrophysical S-function, S(E), and thermonuclear fusion reaction rate, TNFRR (<σv>), at such an extremely low energy, is very challenging for the nuclear astrophysicist community. In the present work, our interest is focused on the study of the variation of S(E) and TNFRR (<σv>) with energy in the cases of few α-trapped fusions. For computations, we adopt the selective resonant tunnelling model (SRTM) technique by following the Khan et al. approach. As an improvement over our previous work, here we invoke the idea of a double-folding potential model. The findings of our computation are compared with some of those available in the literature. Our computed data agrees fairly with the experimentally observed data.